Socio-Economic Prospects of Solar PV Uptake in Energy Policy Landscape of Pakistan - Faraz ul Haq; Tanzeel ur Rashid; Ubaid ur Rehman Zia (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Despite global calls for climate change and its impacts in past decade, energy sector of Pakistan has remained highly dominated by high-cost carbon-intensive resources. Although a significant number of policies have been put forward by both provincial and federal government in last three years, the ground-level implementation of these policies is non-existent, and Pakistan’s progress is still far behind the developed countries. This study therefore performs a socio-economic analysis of solar PV potential in Pakistan and how recent policies can be mobilized to upscale the utilization of solar PV both as an on-grid and off-grid generation source. This also links to solar potential for corporate sector engagements in their Net-Zero Pathways. The methodological approach uses a Low Emission Analysis Platform (LEAP) model designed for Pakistan’s Power System supplies under three different scenarios i.e., Energy Transition Scenario, Conventional Generation Scenarios, and Business as Usual Scenario. Indicative Generation Capacity Expansion Plan (IGCEP 2021) along with recent policies is used as the leading data source for driving the capacity additions. The results obtained from the model indicates that despite having a large potential, under currently policies the share of solar in total grid power generation will remain under 2% by 2030. Under Energy Transition Scenario, the model runs under a least cost optimization plan leading to a higher uptake of solar power. As per this scenario, the share of renewable increase beyond 2030 to achieve a share of around 50% by 2045. This can lead to cumulative carbon reductions of around 2000 Mt by 2030 and economic savings of around 5 billion. Based on the model results, this study also identifies the possible pathways for upcoming iterations of Pakistan IGCEP plan that builds around solar PV